Diagnosis and management of the patient with contaminated illicit drug poisoning - Pino, Richard M.; McGrew, Patrick R. (Frontiers in Anesthesiology, 2023)
The diagnosis and management of poisoning is essential in critical care medicine. Traditionally, these conditions fall under the category of toxidromes that are the signs and symptoms associated with a particular class of poisons. However, there has been a steady increase in designer drugs and contaminants of recreational drugs themselves. Examples of adulterants in cocaine include the local anesthetic benzocaine and the anti-parasitic levamisole. This paper presents the clinical signs, laboratory findings, and treatment of patients who have been exposed to these substances.